Evaluation of an ultra‐lightweight, single‐patient‐use negative pressure wound therapy system over dermal regeneration template and skin grafts. Issue 4 (11th June 2012) - Gabriel, Allen; Thimmappa, Brinda; Rubano, Christopher; Storm‐Dickerson, Toni
Abstract : As the use of negative pressure wound therapy (NPWT) over skin grafts has increased, traditional methods of NPWT system reimbursement and application are increasingly being challenged. A simplified method of accessing and operating NPWT in the outpatient setting is needed, particularly in cases where immediate outpatient use of NPWT is optimal. We evaluated use of a new ultra‐lightweight, off‐the‐shelf, disposable, single‐patient‐use NPWT system (SP‐NPWT; V.A.C.Via™ Therapy, KCI USA, Inc., San Antonio, TX) over dermal regeneration template (DRT) and/or skin grafts. SP‐NPWT was initiated over a DRT and/or skin graft in 33 patients with 41 graft procedures. Endpoints were recorded and compared to a historical control group of 25 patients with 28 grafts bolstered with traditional rental NPWT (V.A.C.® Therapy, KCI USA, Inc.). Average length of inpatient hospital stay was 0·0 days for the SP‐NPWT group and 6·0 days for the control group ( P < 0·0001). The average duration of SP‐NPWT post‐DRT or skin graft was 5·6 days for the SP‐NPWT group and 7·0 days for the control ( P < 0·0001). Preliminary data suggest that, compared to traditional NPWT, off‐the‐shelf SP‐NPWT may provide a quicker, seamless transition to home, resulting in decreased hospital stay and potential cost savings.